BIOPHARMACEUTICAL ASPECTS OF CAPSULIRINE DRUG BASED ON NSAIDs - Kh.M, Yunusova (International Journal of Psychosocial Rehabilitation, 2020)
This report presents the results of a study of the theoretical and experimental justifications for creating compositions based on diclofenac sodium and omeprazole, the main criteria of the approach to developing the composition and technology of capsules with analgesic effects are considered and briefly formulated.